2014
DOI: 10.1039/c3cp55503h
|View full text |Cite
|
Sign up to set email alerts
|

The Ti4 cluster activates water dissociation on defective graphene

Abstract: Activation of the Ti4 cluster on defective graphene for water adsorption and dissociation was investigated via density functional theory. Both the vacancy and the Ti cluster can promote the water dissociation reaction. The vacancy can efficiently enhance the adsorption of Ti atoms to stabilize the cluster. However, compared to the role of the vacancy, the cluster plays a more important role in activating water dissociation. A single water molecule and a second one can almost freely dissociate with (or without)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…We now investigate the adsorption of water at the confined space between G or BG, and TiO 2 . The affinity of water toward G or BG is very low, 75,79,80 thus H 2 O prefers to adsorb on TiO 2 rather than on the carbon sheet, leading to adsorption configurations very similar to those on bare TiO 2 . The B dopant, in this case, has very little influence on the reactivity, as the interaction between H 2 O and G, or BG, is This outcome can be analyzed in more detail by decomposing the binding energies in specific contributions for the different configurations of Figure 10, as reported in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…We now investigate the adsorption of water at the confined space between G or BG, and TiO 2 . The affinity of water toward G or BG is very low, 75,79,80 thus H 2 O prefers to adsorb on TiO 2 rather than on the carbon sheet, leading to adsorption configurations very similar to those on bare TiO 2 . The B dopant, in this case, has very little influence on the reactivity, as the interaction between H 2 O and G, or BG, is This outcome can be analyzed in more detail by decomposing the binding energies in specific contributions for the different configurations of Figure 10, as reported in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous 13,[18][19][20][21][22][23]29,[32][33][34][35][36][37]46 DFT studies of graphene−metal interfaces have been carried out, including calculations that make use of vdW corrections. 40,41,47 However, only few classical MD studies of graphene−metal systems 27,48−50 exist, and to our knowledge, no previous MD studies of graphene− titanium structures have been carried out using classical reactive or nonreactive force fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of graphene–titanium (G–Ti) structures, previous works indicated that Ti chemisorbs to graphene, , adsorbs water when bonded to graphene, has great potential for water dissociation and hydrogen storage, ,, can n- or p-dope graphene, , presents asymmetries in the electron–hole conductance, and manifests high electric contact resistance at the graphene–metal interface. Hence, theoretical descriptions of G–Ti structures at the atomic level are of fundamental importance because they provide knowledge of G–Ti structure–property relationships, which is necessary for the prediction and development of their applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size (diagonal length) in the optimized structure of this framework is found to be 2.204 nm along with the vertical length of 2.597 nm. Ti 4 clusters are one of the stable small Ti clusters. Ti atoms are known to increase the hydrogen adsorption capacity of the host compounds. Small Ti clusters have been efficiently used for hydrogen adsorption in the previous studies. ,, Therefore, a smaller Ti 4 cluster as a linker is considered in this study.…”
Section: Resultsmentioning
confidence: 99%